Skidmore, Owings & Merrill : Architecture and Urbanism 1973-1983 - Bush-Brown, Albert, author 373299; Grube, Oswald W., editor 388931 (New York : Van Nostrand Reinhold, 1983)
SOM's growth as a large architectural firm began almost fifty years ago. By 1981 there were nine offices in the United States with a total of more than 2,100 members. The decade 1973-1983 brought retirement to a number of well-known founding partners. Nevertheless, SOM's reputation for design leadership has been maintained through "creative dissidence", as one of the younger partners describes it. The firm moves with distinction into a third and fourth generation. This book, the third summary volume of SOM's work, reveals the firm's architectural response to a decade that greatly changed American society.